2016
DOI: 10.1371/journal.pone.0155539
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus licheniformis Contains Two More PerR-Like Proteins in Addition to PerR, Fur, and Zur Orthologues

Abstract: The ferric uptake regulator (Fur) family proteins include sensors of Fe (Fur), Zn (Zur), and peroxide (PerR). Among Fur family proteins, Fur and Zur are ubiquitous in most prokaryotic organisms, whereas PerR exists mainly in Gram positive bacteria as a functional homologue of OxyR. Gram positive bacteria such as Bacillus subtilis, Listeria monocytogenes and Staphylococcus aureus encode three Fur family proteins: Fur, Zur, and PerR. In this study, we identified five Fur family proteins from B. licheniformis: tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…S2–S7). The level of His oxidation observed for the three FurA paralogs was comparable to that of PerR proteins treated by H 2 O 2 under the same experimental conditions (Won et al ., ; Kim et al ., ). The high sensitivity of the three FurA paralogs to His oxidation by H 2 O 2 suggests that they are rapidly inactivated by H 2 O 2 through MCHO like PerR proteins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…S2–S7). The level of His oxidation observed for the three FurA paralogs was comparable to that of PerR proteins treated by H 2 O 2 under the same experimental conditions (Won et al ., ; Kim et al ., ). The high sensitivity of the three FurA paralogs to His oxidation by H 2 O 2 suggests that they are rapidly inactivated by H 2 O 2 through MCHO like PerR proteins.…”
Section: Discussionmentioning
confidence: 97%
“…The oxidation status of FurA proteins was analyzed by MALDI‐TOF MS and LC‐ESI MS/MS. As described previously (Kim et al ., ), aliquots of E. coli BL21 (DE3) cells (1.8 ml of cultures of the strains harboring pET29bfurA1, pET29bfurA2 or pET29bfurA3) were treated with either 100 μM H 2 O 2 (final concentration) or the same volume of distilled water for 1 min. Cells were harvested by centrifugation after the addition of 200 μl of 100% (wt/vol) trichloroacetic acid (TCA) solution.…”
Section: Methodsmentioning
confidence: 99%
“…The coexistence of three PerR-like regulators has been reported only in Gram-positive bacteria such as B. licheniformis and M. smegmatis . It was shown that the three B. licheniformis PerRs sense hydrogen peroxide by histidine oxidation, although with different sensitivity [55]. In M. smegmatis , three Fur-like paralogs displayed the canonical PerR Asp residue involved in H 2 O 2 sensitivity, exhibited H 2 O 2 sensing by metal-catalyzed histidine oxidation and a higher H 2 O 2 resistance when their genes were inactivated [56].…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogenase-encoding genes nifHDK, nifS , and nifU responsible for nitrogen fixation in proteobacterial PGPR from Azospirillum, Burkholderia , and Bacillus were used as bait to search for similar sequences (Bruto et al, 2014 ). The pyrroloquinoline quinone-encoding genes pqqBCDEFG in the PGPR Pseudomonas fluorescens F113, Erwinia herbicola , and Enterobacter intermedium (Liu et al, 1992 and Kim et al, 2003 ; Miller et al, 2010 ) were used to mine the studied genomes. The gene encoding the B. velezensis SQR9 3-phytase was selected to mine B. amyloliquefaciens genomes for phytase production (Shao et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%